How Can Psychological Science Inform Research About Genetic Counseling for Clinical Genomic Sequencing?. Issue 2 (9th December 2014) - Khan, Cynthia M.; Rini, Christine; Bernhardt, Barbara A.; Roberts, J. Scott; Christensen, Kurt D.; Evans, James P.; Brothers, Kyle B.; Roche, Myra I.; Berg, Jonathan S.; Henderson, Gail E.
Abstract: Next generation genomic sequencing technologies (including whole genome or whole exome sequencing) are being increasingly applied to clinical care. Yet, the breadth and complexity of sequencing information raise questions about how best to communicate and return sequencing information to patients and families in ways that facilitate comprehension and optimal health decisions. Obtaining answers to such questions will require multidisciplinary research. In this paper, we focus on how psychological science research can address questions related to clinical genomic sequencing by explaining emotional, cognitive, and behavioral processes in response to different types of genomic sequencing information (e.g., diagnostic results and incidental findings). We highlight examples of psychological science that can be applied to genetic counseling research to inform the following questions: (1) What factors influence patients' and providers' informational needs for developing an accurate understanding of what genomic sequencing results do and do not mean?; (2) How and by whom should genomic sequencing results be communicated to patients and their family members?; and (3) How do patients and their families respond to uncertainties related to genomic information?